Nano-sized magnetic Ni particles based dispersive solid-phase extraction of trace Cd before the determination by flame atomic absorption spectrometry with slotted quartz tube: a new, accurate, and sensitive quantification method - Yagci, Ozlem; Akkaya, Erhan; Bakirdere, Sezgin (SPRINGER, 2020)
In this study, a new analytical strategy was developed to determine trace cadmium in aqueous samples with high sensitivity and accuracy. A combination of magnetic nickel nanoparticles (Ni-MNPs) based dispersive solid-phase extraction (DSPE) and flame atomic absorption spectrometry fitted with a slotted quartz tube (SQT-FAAS) lowered the detection limit of cadmium. The magnetic Ni nanoparticles were synthesized, characterized, and thoroughly optimized in a stepwise approach. The quartz tube was custom cut in the laboratory to suit the specifics of the flame burner. Using the optimized conditions, a limit of detection value of 0.58 mu g/L and limit of quantification value of 1.93 mu g/L were obtained. To demonstrate accuracy and applicability of the developed method, well water samples were analyzed for their Cd content, and matrix effect on the extraction yield was investigated. The percent recovery results calculated ranged from 93.8 to 108.2%, with corresponding standard deviation values ranging from 1.7 to 7.7. These results established the developed method as sensitive, accurate, and precise for determination of cadmium at trace levels.
Keywords: Magnetic nickel nanoparticles; Cadmium; Dispersive solid-phase extraction; Flame atomic absorption spectrometry with slotted quartz tube; SAMPLES PRIOR; NANOPARTICLES; PRECONCENTRATION; LEAD; WATER; MICROEXTRACTION; NICKEL; COPPER; FOOD; Environmental Sciences & Ecology